Stereoselective synthesis of pyrrolidines: catalytic oxidative cyclizations mediated by osmium. - Donohoe, T; Churchill, G; Wheelhouse, K; Glossop, P (2006)
(Chemical Equation Presented) A new pathway for oxidative cyclization : N-protected α-amino alcohols with distal alkene units cyclize with complete stereoselectivity and stereospecificity to cispyrrolidines, dependent on the substitution pattern of the starting material. In addition to providing nitrogen- and oxygen-containing heterocycles in good to excellent yields, the catalyst loadings can be reduced to just 0.2 mol% osmium. TMO = Me 3NO, TFA = trifluoroacetic acid, Ts = toluene-4-sulfonyl. © 2006 Wiley-VCH Verlag GmbH and Co. KGaA.